Emerging triple-reassortant influenza C virus with household-associated infection during an influenza A(H3N2) outbreak, China, 2022. Issue 1 (31st December 2023) - Cao, Lan; Lu, Ying; Xie, Chaojun; Chen, Yiyun; Liang, Lijun; Zhou, Tengfei; Zeng, Ziyi; Wen, Chen; Di, Biao; Li, Baisheng; Li, Kuibiao; Zhang, Zhoubin
ABSTRACT: Recent research have shown that influenza C virus (ICV) has a possible higher clinical impact than previously thought. But knowledge about ICV is limited compared with influenza A and B viruses, due to poor systematic surveillance and inability to propagate. Herein, a case infected with triple reassortant ICV was identified during an influenza A(H3N2) outbreak, which was the first report of ICV infection in mainland China. Phylogenetic analysis showed that this ICV was triple reassortant. Serological evidence revealed that the index case might be related to family-clustering infection. Therefore, it is essential to heighten surveillance for the prevalence and variation of ICV in China, during the COVID-19 pandemic.